Curriculum Reform in East Timor: Curriculum Mathematics Primary School - Jaka Wijaya Kusuma; Iwan Junaedi; Mulyono Mulyono; Hamidah Hamidah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
This study aimed to analyze the newly developed math curriculum taking into account the views of teachers and students. Curriculum analysis is realized in three dimensions; (1) Classroom management – the physical and emotional environment of the classroom, the role of teachers and students, and interactions, (2) Instructions – objectives, planning, implementation, methods and techniques, instructional media, and measurement and evaluation, and (3) Strengths (and benefits) and weaknesses (and limitations). Qualitative case study methods are utilized with literature reviews. The responses collected from the sources are the content that is analyzed. These findings suggest that some changes have been made and reflected in the implementation of the classroom, and the student-centered approach has been incorporated into the instruction. Hopefully, it will be the subject of local government discussion in determining the following education policy. On the other hand, some difficulties arise during implementation due to lack of infrastructure